New Hippothoidae (Bryozoa) from Australasia - Gordon, Dennis P. (Zootaxa, 2020)
The diversity of Hippothoidae (Bryozoa, Cheilostomata) in New Zealand is increased from 12 named species to 17 and the number of genera from three to five. New species are recognised in the genera Antarctothoa, Hippothoa, Jessethoa n. gen. and Neothoa (newly discovered in New Zealand waters). A new species of Plesiothoa from New South Wales is also described. Collectively, the new taxa encrust a range of substrata (a catenicellid bryozoan, brown and red macroalgae, rock and mollusc shell). The status of two existing species is changed—Hippothoa divaricata pacifica Gordon, 1984 is raised to full species, and Hippothoa watersi Morris, 1980 is used for putative Hippothoa flagellum in New Zealand. New data are given for these species and Hippothoa peristomata Gordon, 1984, and little-known Antarctothoa buskiana (Hutton, 1873) and Antarctothoa cancer (Hutton, 1873) are illustrated by scanning electron microscopy for the first time.